Development of cost-effective PCM-carbon foam composites for thermal energy storage. (November 2022) - Liu, Xin; Yang, Fangming; Li, Mengbin; Sun, Chenggong; Wu, Yupeng
Abstract: Phase Change Materials (PCMs) has gained considerable interest for storing thermal energy originating from the solar irradiation, industrial waste heat and surplus heat. Here, we present the facile and scalable synthesis of PCM-carbon foam composites by using polyisocyanurate (PIR) foam derived carbon foam as porous support. The unique 3D molecular configuration of the carbon foam materials embedded the composites with high PCM loading capacity, excellent shape stabilization and thermal reliability and chemical stability. The carbon foams prepared by facile chemical activation method with high surface area up to 1968 m 2 /g exhibit high PCM loading capacity of up to 90.8 wt% and excellent energy storage capacity of up to 105.2 J/g. Advanced characterization demonstrated that the total pore volume of carbon foam governs the PCM loading capacity as well as the energy storage performance of the composites. This work provides a potential pathway to recycle PIR foams, which have been widely used in construction industry, by producing cost-effective PCM composites for thermal energy storage.